The value of computerized tomography of the chest in patients with neutropenic fever - AL-Khalissi, Khudhair A; Shukr, Ahmed I; AL-Zubaidy, Azher S (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Absolute neutropenia in hematological malignancies remains the single most important risk factor for infection, which can be fatal and requires urgent management including radiological procedures and treatment.Objectives: To compare computerized tomography (CT) of the chest with chest radiology (CXR) in the assessment of febrile neutropenic patients with hematologic malignancy.Patients and methods: A prospective study, carried out in the hematological ward, Baghdad teaching hospital, for the period from 1stApril 2011to 30thApril 2012.It included 46 neutropenic febrile patients .All had chest X-ray (CXR) and computerized tomography (CT) of the chest.Results: Male were 21, and female were 25. Mean age was 47.89 ± 15.32 years. Mean absolute neutrophil count (ANC) was 0.25X109/L. 29 (63%) patients had normal CXR in which CT was abnormal in 3 of them. 17 (37%) had the same abnormalities on CXR and CT.Conclusion: Computerized tomography is superior to CXR in patients with neutropenic fever, and it should be included in the investigations, especially in patients with respiratory symptoms.